2020
DOI: 10.1080/09588221.2020.1720253
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary learning through videos: captions, advance-organizer strategy, and their combination

Abstract: This study intended to examine L2 young learners' vocabulary learning (i.e. form, meaning, and use). The research design involved a 2 (advance-organizer strategy: present vs. absent) Â 4 (caption type: glossed full captions, glossed keyword captions, full captions, keyword captions) between-subjects design. A total of 240 Chinese ESL primary school students were recruited and randomly and equally assigned to eight conditions. Findings revealed that captioned videos produced significant effects on learning rega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 53 publications
6
35
2
Order By: Relevance
“…With the democratisation and demonetisations of technology, most young learners in this 21st Century have access to the device and infrastructure. It allows them to consume social media, including YouTube [24]. This also happens in Indonesia [49].…”
Section: Youtube and Bilingual Young Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…With the democratisation and demonetisations of technology, most young learners in this 21st Century have access to the device and infrastructure. It allows them to consume social media, including YouTube [24]. This also happens in Indonesia [49].…”
Section: Youtube and Bilingual Young Learnersmentioning
confidence: 99%
“…Various studies have observed how YouTube can improve young learners' vocabulary in their English learning. A survey conducted by [24] investigated how students' English vocabulary increased through YouTube videos [24]. In this research, four short storytelling videos from YouTube, four minutes long for each video were used.…”
Section: Youtube Videos and The Improvement Of Young Learners' Vocabularymentioning
confidence: 99%
“…Both teachers and students need time to adapt to the online learning system (Rasmitadila et al, 2020). Besides, teachers need to improve their skills in applying advance organiser learning model as well as the use of Zoom Meeting applications (Teng, 2020). This is important as an option to deal with the problem of students' motivation in following online learning, according to the findings in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Due to advances in technology, Anaraki's research would likely yield a different result in the current study. This is supported by the research of Teng (2020), who assessed the effect of L2 videos watched on a mobile phone with and without subtitles helping the language acquisition process. Over two-hundred Chinese primary school students were included in the research.…”
Section: Investigations Into the Impact Of Mobile Language Learningmentioning
confidence: 71%
“…The acquisition of the English language is essential for international, cultural and scientific communication, and due to the rapid internationalization developments in education, it is vital for learning in a university intercultural environment. The emergence of new digital technologies greatly aids the language acquisition process and more and more students are using tools and mobile applications to support out-of-school learning (Fűz, 2017;Teng, 2020). Especially in the last four years, language MALL applications have emerged to help language learning, which can effectively help the development of skills (especially listening and reading comprehension).…”
Section: Introductionmentioning
confidence: 99%